2014
DOI: 10.1080/00405000.2014.946341
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the physical properties of elastic-woven fabrics using Grey–Taguchi method

Abstract: Present work was undertaken to study the effects of yarn, fabric, and machine parameters on crease recovery and pilling performance of woven fabrics containing the elastane yarn. In order to estimate the optimum process conditions and examine the individual effects of the controllable factors separately on a particular response, the experiments were performed according to Taguchi's experimental design. Also, to optimize the multiple process responses (crease recovery angle and pills number), Grey-Taguchi metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Some researchers suggested that the elastane linear density and draft ratio were almost equally significant for the mechanical properties of the woven fabrics (Qadir et al, 2014). Physical properties of the elastic woven fabric were predicted and optimized by using the Grey-Taguchi method (Masaeli et al, 2015).…”
mentioning
confidence: 99%
“…Some researchers suggested that the elastane linear density and draft ratio were almost equally significant for the mechanical properties of the woven fabrics (Qadir et al, 2014). Physical properties of the elastic woven fabric were predicted and optimized by using the Grey-Taguchi method (Masaeli et al, 2015).…”
mentioning
confidence: 99%
“…Several research [1][2][3][4][5] have used Taguchi and Grey Relational Analysis (GRA) methods to optimize sizing parameters for good strength of sized yarn. Other studies [6][7][8][9][10], conducted research that focused on optimizing the process condition. The optimization process emphasized on significant factors, such as weft yarn type, fabric design, weft density, air pressure, and shed closing timing.…”
Section: Introductionmentioning
confidence: 99%
“…Original Taguchi method is restricted to a single response, and hence GRA was used in this study for better understanding of responses. This method has been applied to different textile processes and products [40,4244].…”
Section: Introductionmentioning
confidence: 99%